Key Competencies of a Project Manager When Managing A High-Risk Project - Agnieszka JĘDRUSIK (Communications of International Proceedings, 2024)
Competence is a key element in the effectiveness of any business and is the key to the success of an organization. A project manager is a person who should have the right personality traits and skills to lead a project from the initiation phase to the completion phase according to a certain standard that allows the achievement of the set goals. The main purpose of this article is to outline the key competencies that every project manager should possess. There is no clear definition of key competencies in project managers in three areas based on certain standards. For the study was selected a group of project managers from the automotive industry from a medium-sized company located in the Podkarpackie ( southern part of Poland). The article includes a theoretical part containing a description of key competencies in three areas and their analysis based on the study of a group of project managers from the automotive industry.